Preparing Teachers With Sociocultural Knowledge in Literacy: A Literature Review. (June 2019) - Wetzel, Melissa Mosley; Vlach, Saba Khan; Svrcek, Natalie Sue; Steinitz, Erica; Omogun, Lakeya; Salmerón, Cori; Batista-Morales, Nathaly; Taylor, Laura A.; Villarreal, Doris
Although the call for teachers to address the demographic imperative has existed for decades, recently, there has been an uptake of frameworks of multicultural education, culturally responsive pedagogies, critical literacy, and others into literacy teacher preparation. In this study, we examine connections that pre-service teachers make as a result of experiences focused on sociocultural knowledge and literacy and barriers they face in building these connections. Areas of connection include examining one's past; recognizing students' lives and resources in literacy teaching; considering race, racism, and students' racial identity; drawing on multilingualism as a strength of students for literacy learning; and engaging actively and inquiring into literacy.